Four-fold increase in solar forcing on snow in western U.S. burned forests since 1999 - Gleason, Kelly E. (Nat Commun, 2019)
Forest fires are increasing across the American West due to climate warming and fire suppression. Accelerated snow melt occurs in burned forests due to increased light transmission through the canopy and decreased snow albedo from deposition of light-absorbing impurities. Using satellite observations, we document up to an annual 9% growth in western forests burned since 1984, and 5 day earlier snow disappearance persisting for >10 years following fire. Here, we show that black carbon and burned woody debris darkens the snowpack and lowers snow albedo for 15 winters following fire, using measurements of snow collected from seven forested sites that burned between 2002 and 2016. We estimate a 372 to 443% increase in solar energy absorbed by snowpacks occurred beneath charred forests over the past two decades, with enhanced post-fire radiative forcing in 2018 causing earlier melt and snow disappearance in > 11% of forests in the western seasonal snow zone.